(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
— MCM (multicarrier Modulation) works on the concept of splitting a data stream into many bitstreams, each with a significantly low bit rate and modulating the several carriers with sub-streams. Multicarrier modulation schemes such as FBMC and OFDM are used. Spectral efficiency of the FBMC system is higher than the OFDM system. The simulation’s results are used to examine the framework, argumentation, and evaluation of FBMC and its relation to OFDM. Furthermore, we obtain a higher throughput that is similar to the achievable rate, and the results of this study show that Filter bank multicarrier provides a satisfactory performance improvement.